2021
DOI: 10.1007/s00253-021-11482-w
|View full text |Cite
|
Sign up to set email alerts
|

On the nutritional and therapeutic effects of ketone body d-β-hydroxybutyrate

Abstract: d-β-hydroxybutyrate (d-3HB), a monomer of microbial polyhydroxybutyrate (PHB), is also a natural ketone body produced during carbohydrate deprivation to provide energy to the body cells, heart, and brain. In recent years, increasing evidence demonstrates that d-3HB can induce pleiotropic effects on the human body which are highly beneficial for improving physical and metabolic health. Conventional ketogenic diet (KD) or exogenous ketone salts (KS) and esters (KE) have been used to increase serum d-3HB level. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 103 publications
(110 reference statements)
0
10
0
Order By: Relevance
“…This condition pushes the body into ketosis, that is, into a metabolic state characterised by increased concentration of ketone bodies in the blood. Studies on mice with experimental EAE showed the beneficial effects of KDs on disease progression, disability, cognition and inflammatory markers, KDs could reduce the expression of enzymes involved in the biosynthesis of pro-inflammatory molecules [104,105].…”
Section: Ketogenic Dietmentioning
confidence: 99%
“…This condition pushes the body into ketosis, that is, into a metabolic state characterised by increased concentration of ketone bodies in the blood. Studies on mice with experimental EAE showed the beneficial effects of KDs on disease progression, disability, cognition and inflammatory markers, KDs could reduce the expression of enzymes involved in the biosynthesis of pro-inflammatory molecules [104,105].…”
Section: Ketogenic Dietmentioning
confidence: 99%
“…Moreover, serum β-hydroxybutyrate is also considered to be an antitumor agent ( 30 ). Exogenous ketone body intake can reduce atherosclerosis, improve heart failure and protect renal function by inhibiting inflammatory factors ( 31 , 32 ) and improve cognitive function to some extent ( 33 ). Human proximal tubular cells can be directly damaged by high levels of blood β-hydroxybutyric acid (> 20 mmol/L) ( 34 ), while low concentrations of β-hydroxybutyric acid (<10 mmol/L) protect against ischaemic tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…( Newman and Verdin, 2017 ). More importantly, many studies have shown that 3HB has potential therapeutic effects on many diseases ( Yao et al, 2021 ). 3HB and its derivatives could improve the learning and memory capabilities of mice, possibly through a signaling pathway requiring IFN-γ (PUMA-G) by increasing protein synthesis and gap junctional intercellular communication ( Zou et al, 2009 ).…”
Section: Materials Properties Of Phamentioning
confidence: 99%